2022
DOI: 10.1007/s11250-022-03217-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milking environment enrichment through music on production performance and behaviour in cattle

Abstract: Enrichment of milking environment through music has been proposed to help animals to cope with divergent stressors. This study aimed at evaluating the effect of Indian instrumental music-based environmental enrichment on milk production performance and behaviour in cattle. A total of 21 lactating dairy cattle (Vrindavani crossbred cows) having similar parity and stage of lactation were selected in three groups -T1, T2, and T3 each consisting of seven animals. The T1 and T2 groups were exposed to instrumental u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…An increase in the gamma-aminobutyric acid (GABA) content in the blood of cattle, thus promoting the secretion of growth hormones, could also be seen when light music was played (Ma & Wang, 2020). Other studies also found no association between milk yield and music (Kochewad et al, 2022;Lemcke et al, 2021). Even though the highest milk output occurred when no music was played, the cows demonstrated relaxed behaviours such as sleeping and relaxing when some music was played, indicating reduced stress and increased welfare (Kemp, 2020).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…An increase in the gamma-aminobutyric acid (GABA) content in the blood of cattle, thus promoting the secretion of growth hormones, could also be seen when light music was played (Ma & Wang, 2020). Other studies also found no association between milk yield and music (Kochewad et al, 2022;Lemcke et al, 2021). Even though the highest milk output occurred when no music was played, the cows demonstrated relaxed behaviours such as sleeping and relaxing when some music was played, indicating reduced stress and increased welfare (Kemp, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Dairy farms, particularly those with noisy mechanical milking parlours, can benefit from playing slow music to their cows to alleviate stress and increase milk production by up to 3% (Kochewad, 2022;Lemcke et al, 2021). Listening to classical music for a long time has increased milk production in dairy cattle (Dhungana et al, 2018;Ganesh, 2020;Liu et al, 2017;Ma & Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…82 ). Consequently, the authors concluded that music can reduce residual milk by improving the welfare of dairy cows during milking [60].…”
Section: Auditory Stimulation In Dairy Cowsmentioning
confidence: 99%
“…It is also best to avoid heavy metal or a fast tempo over 100 beats per minute [48,49]. It is recommended to have a variety of music [50] and more mellow music such as classical [51] or Indian music [52].…”
Section: Music and Animalsmentioning
confidence: 99%
“…In dairy cattle, music improved moving into a robotic milking unit [48]. Another study showed that dairy cows exposed to music had a faster milking speed and better milk letdown [51,52]. Music that was played before milking had some beneficial effects [53].…”
Section: Music and Animalsmentioning
confidence: 99%